PENGARUH PEMBELAJARAN INTERAKTIF TERHADAP HASIL BELAJAR TEMATIK SISWA KELAS V DI MI ISLAMIYAH PARENG - Minahul Mubin (AT-THULLAB : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2018)
This study aims to determine the effect of interactive learning outcomes on classroom students V MI Islamiyah Pareng. This type of research is a quasi-experimental study using nonequivalent control group design conducted with 6 meetings.The subject of this research is class students V.The instrument used was a multiple choice test and observation to capture student learning outcomes and activities that were previously tested to determine the validity and reliability of the test.. Analysis of data using Ttest one right party. The results showed a significant increase in student learning outcomes in learning activities using interactive models